Pembinaan Dan Kesan Modul Intervensi Kaunseling Kelompok Brief Coping Stress (Briscope) Terhadap Stres Guru Pelatih IPGM - Ali, Mohamad Faizel (2021)
This study aims to develop and examine the effect of the Brief Coping Stress (BrisCope) group counseling module towards stress amongst IPGM trainee teachers. The development of BrisCope Module used the steps proposed in the Model Pembinaan Modul Sidek (MPMS) to produce a module that has high content validity and reliability values.